VAR Analysis of the Exchange Rate Pass-Through Effect in Czech Republic - Borodin, Dmitry; Chrobok, Viktor; Zouhar, Jan, 1982-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2013)
The paper will empirically investigate the strength and the speed of the exchange rate pass-through effect in the Czech Republic, i.e. the change in the domestic prices, originally caused by the volatility of the exchange rate. VAR modelling framework has been chosen as a main instrument of analysis. Vector autoregression will also be the subject of the theoretical part of the paper, which aims to provide a clear and at the same time many-sided discussion on the relevant topics. Practical part will be completely devoted to the modelling of the exchange rate pass-through.
Vedoucí práce: Viktor Chrobok
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: matematické metody v ekonomii [obor bakal. práce]; bakalářské práce; bachelor's theses